2021
DOI: 10.1097/ncc.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

“Doing What Only I Can Do”

Abstract: BackgroundSparse evidence exists regarding the feasibility and patients’ experiences of exercise programs among older cancer populations.ObjectiveThe aim of this study was to explore the experiences of older patients with advanced cancer who participated in a 12-week supervised and multimodal exercise program in a hospital setting.MethodsIndividual interviews were conducted with 18 participants (≥65 years) with advanced cancer who completed the intervention program regardless of compliance rate. In addition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Participants found the hospital environment to be practical as visits could be combined with other health care appointments and provide access to physiotherapists from whom feedback was appreciated ( 20 , 24 ). In addition, they were reassured by being in an environment where there was an understanding of illness and fluctuating performance from day to day.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants found the hospital environment to be practical as visits could be combined with other health care appointments and provide access to physiotherapists from whom feedback was appreciated ( 20 , 24 ). In addition, they were reassured by being in an environment where there was an understanding of illness and fluctuating performance from day to day.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they were reassured by being in an environment where there was an understanding of illness and fluctuating performance from day to day. Mikkelsen et al reported “some” of the 18 participants in their study appreciated the opportunity to co-ordinate visits for exercise programmes with medical appointments, positively influencingtheir capacity to take part because, even on their “bad days”, they had to attend hospital appointments ( 24 ). In Adamsen et al's study of a home and hospital-based exercise intervention participants reported that although the program was easily comprehended, several reasons existed for why they struggled to follow it ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations